Effects of Exosomes Derived From Helicobacter pylori Outer Membrane Vesicle-Infected Hepatocytes on Hepatic Stellate Cell Activation and Liver Fibrosis Induction - Zahmatkesh, Masoumeh Ebadi; Jahanbakhsh, Mariyeh; Hoseini, Negin; Shegefti, Saina; Peymani, Amir; Dabin, Hossein; Samimi, Rasoul; Bolori, Shahin (Frontiers in Cellular and Infection Microbiology, 2022)
Liver fibrosis is a multifactorial disease with microbial and non-microbial causes. In the recent years Helicobacter pylori infection has been thought to play a critical role in some extra-gastrointestinal manifestations especially liver disorders. Outer membrane vesicles (OMVs) are one of the most important discussing H. pylori virulence factors. In the current study, four different clinical strains of H. pylori were collected and their OMVs were purified using ultra-centrifugation. To investigate their effects on liver cell exosomes, co-incubation with hepatocytes were applied. After a while, hepatocyte derived exosomes were extracted and incubated with hepatic stellated cell (HSC) to investigate the HSC activation and fibrosis markers induction. The expression of α-SMA, TIMP-1, β-catenin, vimentin and e-cadherin messenger RNAs (mRNA) was assessed using real-time RT-PCR, and also the protein expression of α-SMA, TIMP-1, β-catenin, vimentin and e-cadherin was evaluated by western blotting. Our results showed, infected hepatocytes-derived exosomes induced the expression of α-SMA, TIMP-1, β-catenin, vimentin in HSCs and e-cadherin gene and protein expressions was down-regulated. In the current study, we found that H. pylori-derived OMVs may aid the exosomes alternation and modified exosomes may have a possible role in HSCs activation and liver fibrosis progression.